Comparison of Time in the World and the Afterday in the Quantum Revolution to the Rules of Islamic Science - Suprima; Muhamad Parhan; Riska Siti Nurjanah; Muhammad Azzara; Ahmad Ihsan Nur Solehudin; Muhamad Rafli Chrismawan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
Time and space are quantities determined by mass and speed. Atom is the smallest material that can not be divided again. The quantum revolution begins with the existence of a wave that has dualistic properties, then discusses micro-objects and their constituents. This has something to do with the comparison of time and the afterlife which is explained through science and the source of truth, namely the Qur'an. The method used is the library research method which focuses on analysis by connecting with the Al-Qur'an. The results of the analysis found that the comparison of the time of the world and the hereafter is explained in the Al-Qur'an in Al-Hajj verse 47 and Al-Baqarah verse 80, it is explained that the world time is faster than the time of the Hereafter which is associated with quantum physics is the assumption that this world is like an atom and the next world is a large dimension, so the time in the two will be very clearly different. The afterlife will slow down because the calculation of world time will be much faster because the world is small like an atom. Atom itself is explained in the letter Al-Zalzalah verses 7-8, the letter Yunus verse 61, and the letter An-Nisa verse 40.